H. S. SKOVORODA AND UKRAINIAN EDUCATION: YESTERDAY, TODAY, TOMORROW - Прокопенко, Іван (New Collegium, 2020)
The article is devoted to the retrospective analysis of educational views of the outstanding Ukrainian educationalist, philosopher, teacher, and writer H. S. Skovoroda (1722–1794). The article contains a brief analysis of views and educational tools, developed by H. S. Skovoroda while teaching in Kharkiv Collegium from 1759 till 1769 as well as to the great number of philosophical and edu cational works written after 1769. The necessity to use H. S. Skovoroda theoretical heritage under the conditions of reformation of educa-tion in modern Ukraine is grounded.